Analisis Kepuasan Konsumen Sepeda Listrik Merek Goda - Mukhyidin Mukhyidin; Ade Ifan Mujayanto; Syamsul Hidayat (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
The development of environmentally friendly transportation facilities is currently being intensively carried out by automotive companies throughout the world, which is an action taken from the issue of global warming, namely to reduce pollution and aims to overcome the increasing shortage of non-renewable petroleum fuels. One of the means of transportation currently being developed is electric vehicles. Of the various types of electric vehicles being developed, electric bicycles are the most popular and most successfully developed, especially in European countries and China. The aim of this research is to analyze consumer satisfaction in using Goda brand electric bicycles among Bina Bangsa University students in Serang City. The research sample consisted of 72 respondents. The data collection method used in this research is a questionnaire. This research method is quantitative with data analysis techniques using validity and reliability tests. Thus, this approach will allow analysts to find out the extent of consumer behavior regarding consumer satisfaction in using Goda brand electric bicycles among Bina Bangsa University students.